2022
DOI: 10.1155/2022/3290479
|View full text |Cite|
|
Sign up to set email alerts
|

PRR15 Is a Novel Diagnostic and Prognostic Biomarker in Papillary Thyroid Cancer and Modulates the Tumor Microenvironment

Abstract: Papillary thyroid cancer (PTC), accounting for more than 80 percent of all cases of thyroid cancer, is a form of a cancerous tumor that has a very favorable prognosis. However, patients diagnosed with PTC who are already in an advanced state have a dismal outlook. This study aimed to establish the diagnostic relevance of PRR15 expression in PTC patients as well as its levels in PTC samples and its connection with immune infiltrates. The TCGA and GEO datasets were combed through to obtain information on PTC pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…The low expression of SLC4A4 in thyroid cancer, and its diagnostic value, is associated with lymph node in ltration and distant metastasis in colon adenocarcinoma patients, and it may be a biomarker and prognostic diagnostic and therapeutic target of colon adenocarcinoma [23]. Increased expression of SLC4A4 in β cells of type 2 diabetes plays an important role in promoting β -cell exhaustion, and should be regarded as a potential therapeutic target [24].…”
Section: Discussionmentioning
confidence: 99%
“…The low expression of SLC4A4 in thyroid cancer, and its diagnostic value, is associated with lymph node in ltration and distant metastasis in colon adenocarcinoma patients, and it may be a biomarker and prognostic diagnostic and therapeutic target of colon adenocarcinoma [23]. Increased expression of SLC4A4 in β cells of type 2 diabetes plays an important role in promoting β -cell exhaustion, and should be regarded as a potential therapeutic target [24].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with differentiated thyroid carcinoma have an excellent prognosis. However, minority of patients show a dismal course with tumor recurrence and mortality rate less than 5% (Elsayed et al, 2020;Lingli Wang et al, 2022). The treatment includes surgery usually followed by radioiodine ablation and hormone treatment (TSH suppression therapy) according to the guidelines of the American Thyroid Association (ATA) and European Association of Nuclear Medicine (EANM) (Schmidbauer et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%